2012
DOI: 10.3354/ab00423
|View full text |Cite
|
Sign up to set email alerts
|

Diadromous life cycle and behavioural plasticity in freshwater and estuarine Kuhliidae species (Teleostei) revealed by otolith microchemistry

Abstract: Otolith microchemistry and microstructure were examined in juveniles of 3 Kuhlia species (Teleostei) from fresh and brackish environments in order to examine their migratory histories. All species presented with strontium:calcium (Sr:Ca) and barium:calcium (Ba:Ca) profiles in the inner region of the otoliths that suggested an obligatory marine larval phase. At approximately 0.3 to 0.6 mm from the otolith core, all individuals showed a sharp increase in Ba:Ca ratios that were generally associated with variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…Recent studies have found that some individuals within species (Kuhlia malo, K. rupestris, Kuhlia munda, and Kuhlia xenura) are polytypic for migratory traits, and this primarily occurs with juvenile life stages (Benson and Fitzsimons 2002;Feutry et al 2011Feutry et al , 2012aMcRae et al 2011). In addition, juveniles of Kuhlia caudavittata and K. mugil are sometimes captured in freshwater (P. Feutry, personal observation).…”
Section: Ancestral Character States Reconstructionmentioning
confidence: 99%
“…Recent studies have found that some individuals within species (Kuhlia malo, K. rupestris, Kuhlia munda, and Kuhlia xenura) are polytypic for migratory traits, and this primarily occurs with juvenile life stages (Benson and Fitzsimons 2002;Feutry et al 2011Feutry et al , 2012aMcRae et al 2011). In addition, juveniles of Kuhlia caudavittata and K. mugil are sometimes captured in freshwater (P. Feutry, personal observation).…”
Section: Ancestral Character States Reconstructionmentioning
confidence: 99%
“…This result is principally verified by Paragamian & Wakkinen (2008) who reported multiple burbot movement patterns in a river-lake system of North America, using telemetry and limited sample size. Although widespread in salmonids (e.g., Thorpe 1994), it is only recently when such examples amongst nonsalmonid fish have emerged (Daverat et al 2006(Daverat et al , 2012Feutry et al 2012). For example, Daverat et al (2012) have shown that European flounder Platichthys flesus may spawn in coastal, brackish or freshwater environments, and multiple habitat use patterns exist.…”
Section: Burbot Life Historymentioning
confidence: 99%
“…In some areas, however, Sr:Ca in a low-salinity environment may exceed that of high (Kraus & Secor 2004). Several studies have also used barium to calcium ratio (Ba:Ca) as a tracker of fish migratory history (Elsdon & Gillanders 2005;Feutry et al 2012). Several studies have also used barium to calcium ratio (Ba:Ca) as a tracker of fish migratory history (Elsdon & Gillanders 2005;Feutry et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies on Gobiidae have revealed a check-mark deposition at the time of post-larval recruitment linked to a decrease in the calcareous growth rate (Shen and Tzeng 2002;Keith et al 2008). The number of increments between the core and the metamorphosis check mark is therefore an estimation of their pelagic larval duration (PLD) (Yamasaki et al 2007;Feutry et al 2012). The elemental composition of the otolith is used to reconstruct the migratory environmental history (Daverat and Tomas 2006;Shiao et al 2006).…”
Section: Introductionmentioning
confidence: 99%